REVITALISASI MANAJEMEN WAKAF SEBAGAI PENGGERAK EKONOMI MASYARAKAT - Munir, Zainal Arifin (Fakultas Syariah, 2013)
Mobilize sectors of the society economy with waqf instrument is very rasional. According data compiled by the Ministry of Religious Affairs, the number of waqf land in Indonesia reached 2,686,536,656, 68 square meters or 268,653.67 acres 366 595 locations spread across an area Indonesia. With a large area, it will contribute to socio-economic empowerment if it is managed with proper and professional management. This is the most urgent matter to be addressed in the management of waqf is nadzir professionalism, because they are the key to successful management of endowments to be more focused, productive and strategic. As one of the sharia instruments, the management of waqf should be rightfully optimized for development the welfare of society. Menggerakkan sektor ekonomi masyarakat dengan instrument wakaf adalah sangat rasional.Menurut data yang dihimpun Departemen Agama RI, jumlah tanah wakaf di Indonesia mencapai 2.686.536.656, 68 meter persegi atau 268.653,67 hektar yang tersebar di 366.595 lokasi di seluruh Indonesia. Dengan lahan seluas itu, tentunya akan sangat berkonstribusi dalam pemberdayaan social ekonomi jika dikelola dengan manajemen yang tepat dan profesional. Inilah hal yang paling urgen untuk dibenahi dalam pengelolaan wakaf adalah profesionalisme nadzir, karena mereka merupakan kunci keberhasilan pengelolaan wakaf agar lebih focus, produktif dan strategic. Sebagai salah satu instrument syariah, manajemen wakaf sudah seharusnya dioptimalkan pengelolaannya untuk peningkatan kesejahteraan masyarakat.